A Note on the Interdependent Structure of Security Returns - Lee, Cheng F. (Journal of Financial and Quantitative Analysis, 1976)
S-L have derived a simultaneous equation CAPM to offer a robust test for the interdependent assumption of the single equation CAPM. However, their empirical results are subject to the multicollinearity problem associated with 2SLS. For improving their results, several alternative estimation methods are used to estimate a seven-equation system for the oil industry. In accordance with both the multicollinearity criterion and residual analysis, it is found the modified 2SLS is the most appropriate method to be used to estimate the S-L model. From the results obtained from the modified 2SLS, it is shown that the market rate of return still is a relatively important factor in predicting the movement of capital market in the simultaneous equation CAPM. After applying a better estimation method to the S-L simultaneous equation CAPM, it is shown that the S-L model has given us the interesting interrelationship of capital asset pricing within a particular risk class.